2019
DOI: 10.1186/s13047-019-0367-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of foot ulceration with quality of life and psychosocial determinants among patients with diabetes; a case‐control study

Abstract: BackgroundPatients with diabetic foot ulcers may have a lower quality of life. The objective was to compare the quality of life and its psychosocial determinants among patients with and without diabetic foot ulcers.MethodsA case-control study was conducted in 2017 among patients with (cases) and without (controls) diabetic foot ulcers. The study tools included the World Health Organization’s Quality of Life scale (WHOQOL-BREF), the Hospital Anxiety and Depression (HAD) scale for anxiety and depression, the Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
14
0
2
Order By: Relevance
“…Despite efforts to reduce this disease menace in African countries, global projections have shown that the Africa continent will experience the most significant future increase in the burden of DM of about 156% by 2045 (Federation, 2017). Many studies have demonstrated that most individuals affected with diabetes experience higher anxiety, depression, and frustration than ordinary people (Alosaimi et al, 2019). Among these disorders, depression has been reported as the second mental disorder globally.…”
Section: Introductionmentioning
confidence: 99%
“…Despite efforts to reduce this disease menace in African countries, global projections have shown that the Africa continent will experience the most significant future increase in the burden of DM of about 156% by 2045 (Federation, 2017). Many studies have demonstrated that most individuals affected with diabetes experience higher anxiety, depression, and frustration than ordinary people (Alosaimi et al, 2019). Among these disorders, depression has been reported as the second mental disorder globally.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the prevalence and effect of pain on the quality of life in diabetic foot syndrome (DFS) patients showed results that most often refer to patients with neuropathic pain 16 and/or coexisting foot ulceration, 17 however, there are no studies on the influence of pain on the quality of life in patients with diabetes and post-amputation diabetic foot syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Also a question related to the assessment of the incidence of pain in the postoperative wound and/or the residual limb was asked. Pain intensity measurements were taken at baseline for all patients 7 days, 6 months and 12 months after surgery using a 10 cm VAS, 17 , 18 , 19 where 0 indicates no pain and 10 corresponds to the worst pain imaginable - the measurement was always performed by the researcher or a person trained by him.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the severity of somatic symptoms in the current study was very similar to that for Saudi patients with diabetes. 45 …”
Section: Discussionmentioning
confidence: 99%
“…However, psychosocial disorders, especially depressive and anxiety symptoms, were associated with poor QoL among patients with diabetes, skin disease, and sickle cell disease. 45 - 47 …”
Section: Discussionmentioning
confidence: 99%